2020
DOI: 10.1108/mhrj-10-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Mental health interventions in the mining industry: a narrative review

Abstract: Purpose Previous research has suggested high levels of unaddressed mental health needs among male-dominated work settings. The mining industry has been a recent focus internationally. This paper aims to critically examine research regarding organizational mental health interventions for people working in mining industries. Design/methodology/approach The narrative review used a systematic standardized search strategy in six databases and grey literature from 1990 to 2019. Findings Of the 418 studies identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The intervention group completed the psychological questionnaires a third time 3 months later. The 3-month follow-up for the intervention group was established of the basis of the analysis of other psychological interventions ( Asare-Doku et al, 2020 ; King et al, 2005 ), as well as methodological recommendations ( Guidi et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The intervention group completed the psychological questionnaires a third time 3 months later. The 3-month follow-up for the intervention group was established of the basis of the analysis of other psychological interventions ( Asare-Doku et al, 2020 ; King et al, 2005 ), as well as methodological recommendations ( Guidi et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Job stressors such as high noise exposure, shift work, and production occupations (all highly prevalent in the mining industry) have all been linked to hypertension. 2,[21][22][23][24] Further study is needed to determine if miners have a higher prevalence of hypertension than other workers in the early working years, and, if so, the contributing factors.…”
Section: Educationmentioning
confidence: 99%
“…Furthermore, a broad study of resource workers found that one-third reported moderate-severe depression [15]. Of further concern is that there remains a stigma surrounding mental health in the resource sector, which makes workers less likely to seek support [16]. In mining and construction workers in remote areas of Australia, 40% perceived there was a stigma surrounding mental health and 39% reported that help was unavailable when needed.…”
Section: Prevalence Of Mental Health Complaintsmentioning
confidence: 99%
“…What is recommended within the framework, however, is that, at times where healthcare needs are lower, other activities may be conducted such as health promotion and occupational health services [26]. This recommendation aligns with a significant volume of published evidence which has demonstrated that preventative healthcare strategies such as interventions targeting behaviour change and employee well-being at the organisation level can have significant benefits to employee wellness and health status [16,27,28].…”
Section: Primary Healthcarementioning
confidence: 99%